SOSIALISASI DAN EDUKASI INOVASI ARMADA TERAPUNG (ARUNG) UNTUK MENINGKATKAN KESEJAHTERAAN NELAYAN TRADISIONAL DESA COT SEURANI, KABUPATEN ACEH UTARA - Shadiqin, Imam; Salmarika, Salmarika; Hafli, T. Mudi; Noviyansyah, Bagas; Amir, Fachrurozi; Khatami, Syahril (Universitas Mataram, 2025)
The limited fishing fleet has become a major problem for small-scale fisheries in many regions of Indonesia, one of which is Cot Seurani Village, Muara Baru District, North Aceh Regency. Due to the lack of fishing fleets, many fishers in Cot Seurani Village have to find other jobs to make ends meet. If this situation is allowed to continue, it will inhibit the development of the marine and fisheries sector as well as the welfare of local fishers. To address the above issues, Armada Terapung (Arung) serves as an alternative platform for fishers to conduct fishing activities and can be utilized as a potential fishing area. The objective of this activity is to socialize and educate fishers about ARUNG as a platform for fishing activities. The methods used in this activity include socialization and education for fishers community through three stages: preparation, implementation, and evaluation. The result of this activity is that the Arung technology socialization and education activities were carried out well executed and received a positive response from all participants. The partner groups gained a good understanding of the general overview of Arung, its functions, construction, and how it can be optimally utilized by all parties. The safety of fishers during fishing activities on Arung is an important consideration during the construction of Arung. The conclusion of this activity is that the socialization and education of fishers on Arung technology has provided fishermen with a good understanding and has provided a lot of positive input for the development of Arung's design before it is put into operation.